Royal presence at universiti's Hari Raya open house - Roslina, Mohamad (Star Media Group, 2010)
Some 4000 student and staff members of Universiti Malaysia Pahang (UMP) attended the university's Hari Raya Aidilfitri open house which was graced by Sultan of Pahang Sultan Ahmad Shah and Sultanah of Pahang Sultanah Kalsom